The Effectiveness of a Teaching Strategy Based on Results of Brain Research in the Achievement of Science among Seventh Grade Students and their Motivation to Learn it - Ahlam Hamdoun; Ramzi Haroun (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to investigate the effectiveness of a developed teaching strategy based on the results of brain research in the achievement of seventh grade female students in science and their motivation towards learning it. Its sample consisted of (66) female students in the seventh grade at Kasbah Amman Governmental Schools, divided into two groups: a control group (n=33) taught using a usual method, and an experimental group (n=33) taught using a developed teaching strategy based on the results of brain research. The teaching lasted over twenty lessons in the first semester of the 2018/2019 academic year. An achievement test to measure female students' achievement in science and a motivation scale to measure the students' motivation towards learning science were prepared. The results showed a positive effect of employing a developed teaching strategy based on the results of brain research on the achievement of seventh grade female students in science and their motivation towards learning it. In light of these results, the researcher recommends the adoption of this developed strategy by the Ministry of Education in Jordan.